Perancangan Sistem Planned Maintenance dan Man Power Planning di PT X - Soebiantoro, David; Halim, Siana (Jurnal Titra, 2013)
The purposes of this thesis are designing a planned maintenance and man power planning in the maintenance department of PT X Previously, the PT X used breakdown and corÂrecÂtive maintenance. The maintenance procedures will be revised into corrective mainÂtenance and when continuous proÂduction system is executed, corrective & preventive maintenance will be applied. For defining those procedures, first we identified the machinesâ failure and redesignÂed the production system. Additionally, we propose four level of man power planning based on their skill and company management want it divide into four level.